Special Issue: Passion of the Christ - Editorial - Blizek, William L. (The journal of religion and film, 2004)
On January 29, 2004, The Journal of Religion and Film and The Center for the Study of Religion and Society sponsored a day long symposium on the issues that have been raised by the soon to be released Mel Gibson movie, The Passion of the Christ. The symposium was hosted by Creighton University and The University of Nebraska at Omaha. The morning sessions were held on the University of Nebraska at Omaha campus and the afternoon sessions were held on the campus of Creighton University. The papers published in this special edition were presented at that symposium on 29 January, 2004.